DEIKSIS PRONOMINA DEMONSTRATIF KO-SO-A PADA SOAL DOKKAI JLPT N4 - Mustika, Aldilla; Hermandra, Hermandra; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research to know the used of deixis in dokkai text, then describe the results of analysis on the use of the Japanese language demonstrative pronoun ko-so-a, and to find out the meanings and functions in dokkai text. The method used in this research is a qualitative descriptive method that focuses on a problem related to individuals, phenomenal, documents, and social symptoms. The data collection technique that will be carried out in this research is to select the object of this research and then only selected sentences that contain ko-so-a demonstrative pronoun deixis on the dokkai text in JLPT N4 questions. The results showed that in 7 (seven) document texts on JLPT N4 questions selected as research objects there is 4 types of demonstrative pronouns use deixis, there are 3 demonstrative pronouns of object words, 2 demonstrative pronouns words pointing place, 2 demonstrative pronouns of actions, 6 demonstrative anaphoris pronouns. And from 7 dokkai text analysis there are 5 times show of demonstrative dexis ko, 2 time of kore demonstrative pronouns, 1 time demonstrative dexis koko, 2 times of demonstrative pronounced dexis kono. Then 6 times the show of demonstrative dexis so, 3 times the show of demonstrative pronouns deixis soko, and 3 times the appearance of dexis demonstrative pronouns sono. And then 1 of demonstrative deixis pronoun a is ano.Key Words: Deixis,Demonstrative Pronoun,Dokkai,JLPT N4.